Determinants of Mobile Wallet Intentions to Use: The Mental Cost Perspective. Issue 10 (15th June 2019) - Chatterjee, Debmallya; Bolar, Kartikeya
ABSTRACT: Mobile wallet has become the predominant form of electronic commerce in many countries, and India is no exception. It is imperative to understand the behavior of users of mobile wallets as it can help service providers to attract new users and retain their existing ones. For predicting intentions to use from a mental cost perspective, this empirical study focuses on evaluating different competing models using relevant, vital constructs rooted in theories of Diffusion of Innovation, Planned Behavior, and Technology Acceptance Model and Trust. Results point to the supremacy of the Perceived Behavioral Control construct over other constructs in predicting the intentions, to use mobile wallets. Among the competing models, the best predictive model explained 50.81% of the changes in intentions to use.